Assessment of the accuracy of scaling methods for radiance simulations at far and mid infrared wavelengths. (September 2021) - Martinazzo, Michele; Magurno, Davide; Cossich, William; Serio, Carmine; Masiello, Guido; Maestri, Tiziano
Highlights: An accurate computation of the Chou approximation and parametrized formulas of the backscatter parameters are provided for liquid water clouds and ice clouds composed of aggregates hexagonal columns. The accuracies of the Chou approximation and of the Similarity Principle are evaluated by comparison with full scattering solutions for a broad set of conditions involving liquid water clouds, ice clouds and aerosols. For the first time an assessment of the error in the upwelling radiance computation when using scaling approximate radiative transfer methods is provided in the far infrared spectral region. Abstract: Top of the atmosphere synthetic spectral radiances are computed for widespread atmospheric conditions by alternatively using the discrete ordinate algorithm solution or approximate methodologies where the scattering effects are simulated by appropriate scaling of the absorption properties of the diffusive layers. The residuals between the full scattering solution and the scaling methods are evaluated at far- and mid- infrared wavelengths and compared with the goal noise of the FORUM (Far-infrared Outgoing Radiation Understanding and Monitoring) satellite sensor, that will be the next European Space Agency (ESA) 9 t h Earth Explorer, capable of spectrally resolved measurements in the 100–1600 cm − 1 band. The results define the limit of validity of the fast methodologies considered: the Chou approximation, that is provided as an improved version, and a simple scaling based on the similarity principle. In particular, it is shown that in case of water clouds the scaling methodologies are sufficiently accurate in the mid infrared, except when very small effective radii are accounted for, independently of the cloud optical depths. The same holds in the far infrared for low level water clouds and for humid regions, while not negligible inaccuracies are observed in an increasingly dry atmosphere above the cloud and for small effective radii. Ice clouds are accurately simulated by scaling methods at mid infrared wavelengths in all conditions and for very optically thin clouds at far infrared. Nevertheless, the computational errors become larger than the FORUM noise for optical depths of the order of unity at far infrared. Examples of desert dust and volcanic aerosol are also analysed, showing that the approximate solutions could drive to significant errors also at mid infrared wavelengths.